Razjede in njihovo celjenje pri pacientih po amputaciji - Petkovšek Gregorin, Romana (Obzornik zdravstvene nege, 2021)
Introduction: The most common causes affecting the healing of ulcers in patients after amputation are associated with peripheral arterial disease, diabetes and chronic venous insufficiency. The purpose of the study was to identify the factors that may affect the healing of the ulcer on the amputation stump. Methods: Quantitative non-experimental research methodology was used. A retrospective study was performed by reviewing the nursing documentation on ulcer monitoring. The study included 134 patients with an ulcer after amputation of the lower limb, hospitalized in 2017. Descriptive statistics and logistic regression were used. Results: 134 patients had ulcers caused by various factors. In comparison to men, women are more expected to have ulcers at discharge (OR = 4.8, 95 % CI: 1-22), and patients who had an ulcer before the hospitalization (OR = 7.7, 95 % CI: 3-19.2) as well as those with more than one ulcer (OR = 4.7, 95 %, CI: 1-22.3). Patients who had an ulcer on the amputation stump, had lower prospects for the presence of ulcers at discharge from the hospital (OR = 0.2, 95 % CI: 0.1-0.6, p = 0.004). Discussion and conclusion: The findings suggest that at discharge women are more likely to have an ulcer at discharge than men. Also, patients with ulcers at admission and patients with multiple ulcers at admission are more likely to have an ulcer at discharge. A survey including more patients should be conducted. Also, exact monitoring parameters should be specified.
Keywords: nursing; poškodba kože; razjede; skin damage; stres; treatment; ulcers; zdravljenje; zdravstvena nega